Comparative analysis of home environment characteristics: A study of urban and rural farming adolescents - Patra, Kshiptimayee; Patra, Chinmayee; Mohanty, Biswajit; Mahapatra, Subrat Kumar (Plant Science Today, 2026)
Home environment constitutes a fundamental determinant in influencing adolescents’ emotional well-being, social competence and scholastic achievement. The present study examines and contrasts multiple factors of home environmental conditions experienced by adolescents residing in urban versus rural agricultural communities. Through random sampling methodology, a total of 200 participants ranging from 13 to 18 yr of age were selected. For collecting the response, a validated Home Environment assessment instrument that evaluated multiple domains, including parental emotional regulation, scholastic encouragement, family communication patterns and disciplinary approaches, was utilised. The findings demonstrate meaningful variations across numerous home environment characteristics like control, protectiveness, social isolation, deprivation of privileges, conformity, rewards, nurturance, rejection, permissiveness and social desirability. when comparing urban and rural adolescent populations. Particularly noteworthy were gender-related differences observed in several environmental dimensions between these two geographical contexts. It concludes that both urban and rural respondents present distinctive advantages and obstacles that shape adolescent development in unique ways.